The means to kill essays on the interdependence of war and technology from ancient Rome to the age of drones - Dworok, Gerrit 1983-; Jacob, Frank 1984- (McFarland & Company, Inc., Publishers, 2016)
"Throughout human history, technological innovation has functioned as a driver of civilization and inspired many people's belief in progress. Featuring conference papers and articles by specialists in military history from around the world, this collection of new essays examines the interdependence between war and technology from a number of regional perspectives"...